Effect of lysophosphatidylcholine on expression of vascular endothelial growth factor in ECV304 cells - Zhang Li; Rui Yao-Cheng; Qiu Yan; Li Tie-Jun (Acta Pharmacologica Sinica; Vol 22, No 4 (Apri 2001): Acta Pharmacologica Sinica, 2016)
Aim: To determine the effect of lysophosphatidylcholine (LPC) on the expression of vascular endothelial growth factor (VEGF) in human umbilical veins endothelial cell line (ECV304). Methods: VEGF protein production from ECV304 cells was determined by enzyme-linked immunosorbent assay (ELISA). VEGF protein and its receptor were also examined by immunohistochemical staining. After culturing for 24 h with LPC, VEGF mRNA expression in ECV304 was examined by in situ hybridization. Results: Cultured ECV304 cells could express VEGF receptor and a strong expression of VEGF receptor was induced by LPC 5 mg/L. LPC upregulated VEGF protein secreted from the ECV304 cells in a time- and concentration-dependent manner and LPC also stimulated VEGF mRNA expression in the ECV304 cells. Conclusion: LPC could induce a strong expression of VEGF in ECV304 cells.